The Effectiveness of Leadership Learning Interventions in a Local Government Municipality in Mpumalanga Province, South Africa - Isabirye, Anthony; Moloi, Khadija; Mkhabela, Zondi (JISR management and social sciences & economics, 2024)
This study explores the effectiveness of leadership learning interventions in a local government municipality in Mpumalanga province, South Africa, through the lenses of the selected participants. Guided by the adapted staff development framework as developed by Isabirye (2015), the researchers employed a qualitative approach; conducting in-depth interviews with a sample of seven municipal managers who participated in leadership learning interventions. Although the findings reveal the benefits derived from these interventions, the current study high lights the shortcomings of the interventions as revealed by the informants. For example, lack of tailored programmes and materials for financial management as well as insufficient time for learning. From the analysed data, the researchers suggest strategies and techniques that could enhance the effectiveness of leadership learning interventions in a local government setting. The strategies and techniques included among others, the importance of tailored approaches, continuous evaluation, the need for municipal support, and ample time to ensure the desired outcomes. These findings contribute to the existing literature on leadership development and provide practical recommendations for local government municipalities seeking to improve leadership effectiveness and organisational performance, through learning interventions.